PDCT-16. A PHASE I STUDY OF SUBEROYLANILIDE HYDROXAMIC ACID (SAHA) WITH TEMSIROLIMUS IN CHILDREN WITH NEWLY DIAGNOSED OR PROGRESSIVE DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) - Khatua, Soumen (Neuro Oncol, 2019)
Diffuse intrinsic pontine glioma (DIPG) in children remains essentially incurable with a median survival of 12 months. Radiation therapy is currently the standard treatment modality. To date chemotherapy or biologic agents have had no meaningful increase in survival. Data from biopsied DIPG showed the PI3K/AKT/mTOR pathway as a major oncogenic player. Thus targeting these pathways with mTOR inhibitors could hold promise. Genomic and epigenetic insights have shown the role of histone deacetylase (HDAC) in these tumors. Both temsirolimus (mTOR inhibitor) and SAHA (HDAC inhibitor) are well described in pediatric clinical trials with an established maximum tolerated dose (MTD) for phase II studies. This is the first ongoing phase I multi-targeted therapeutic study, in pediatric DIPG, using SAHA and temsirolimus in a combinatorial approach, targeting the key oncogenic pathway and molecules (NCT02420613 currently recruiting). Patients with a performance score of 50 or greater, with newly diagnosed (Stratum I), or progressive (stratum II) DIPG will be eligible. Biopsy is not mandatory. A standard 3 + 3 design is being used for this study. 1 dose escalation and 2 dose de-escalations are permitted beyond the starting dose level. In stratum I patients receive radiation therapy concurrently with vorinostat on the days of radiation, followed by adjuvant therapy with vorinostat and temsirolimus for 10 cycles if they do not have progressive disease. In stratum II patients receive vorinostat and temsirolimus for 12 cycles (28 day cycle), if they do not have progressive disease. Correlative studies evaluating histone acetylation, phosphorylated 70S6K and Akt are being performed. Currently 5 patients have been enrolled, and the study is at the dose escalation level with no dose limiting toxicity (DLT) seen so far. Safety, adverse effects, biological correlatives, and clinical outcomes will be reported once study is completed.